Working with groups - BECKER, Lily (Social Work/Maatskaplike Werk, 2014)
This valuable addition to the group work literature focuses on the integration of theory and practice of group work in the South African context. The communication network that is set up in groups, be it be conflict resolution groups, therapeutic groups or support groups, becomes a vital channel through which the work of the group is done. The important facet of group work practice, namely the interface between individuals, families, communities and the broader society, also receives attention in this book. The learning objectives formulated for every chapter give an indication of what can be expected in a particular chapter, and this can be regarded as an excellent way of adding to the scientific value of the book